Informing Durable Solutions for Internal Displacement in Nigeria, Somalia, South Sudan, and Sudan : Overview - World Bank Group (World Bank, Washington, DC, 2019)
Understanding forced displacement and developing effective solutions requires closing several critical gaps in the data. With forced displacement rising worldwide, the body of work on displacement is growing rapidly. Data on internally displaced persons (IDPs) are particularly problematic, as the distinction between IDPs and internal migrants are not consistent across countries, and as the presence and number of IDPs is often politicized. While efforts have been made to create standardized frameworks for collecting quantitative data on forced displacement, important data gaps persist. This study helps to close data gaps by using micro-level data to profile IDPs. The report uses micro-data, defined as individual and household-level data that is collected directly through personal interviews. Comprehensive micro-data surveys cover IDP populations in four countries in Sub Saharan Africa: Nigeria, Somalia, South Sudan, and Sudan. The micro-data surveys represent IDPs, refugees, and non-displaced populations. The analysis is guided by the durable solutions indicator framework while the policy insights focus on overcoming displacement-induced vulnerability. The analysis examines the demographic structure of IDP and resident populations and draws on reasons triggering displacement.